Maintenance of the enteric stem cell niche by bacterial lipopolysaccharides? Evidence and perspectives - Schuster, Anne (Blackwell Publishing Ltd, 2014)
The enteric nervous system (ENS) has to respond to continuously changing microenvironmental challenges within the gut and is therefore dependent on a neural stem cell niche to keep the ENS functional throughout life. In this study, we hypothesize that this stem cell niche is also affected during inflammation and therefore investigated lipopolysaccharides (LPS) effects on enteric neural stem/progenitor cells (NSPCs). NSPCs were derived from the ENS and cultured under the influence of different LPS concentrations. LPS effects upon proliferation and differentiation of enteric NSPC cultures were assessed using immunochemistry, flow cytometry, western blot, Multiplex ELISA and real-time PCR. LPS enhances the proliferation of enteric NSPCs in a dose-dependent manner. It delays and modifies the differentiation of these cells. The expression of the LPS receptor toll-like receptor 4 on NSPCs could be demonstrated. Moreover, LPS induces the secretion of several cytokines. Flow cytometry data gives evidence for individual subgroups within the NSPC population. ENS-derived NSPCs respond to LPS in maintaining at least partially their stem cell character. In the case of inflammatory disease or trauma where the liberation and exposure to LPS will be increased, the expansion of NSPCs could be a first step towards regeneration of the ENS. The reduced and altered differentiation, as well as the induction of cytokine signalling, demonstrates that the stem cell niche may take part in the LPS-transmitted inflammatory processes in a direct and defined way.